2017
DOI: 10.7150/jca.19130
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of RPS9 Inhibits Osteosarcoma Cell Growth through Inactivation of MAPK Signaling Pathway

Abstract: Objectives: Osteosarcoma is the most common malignant bone tumor in adolescents; however, the mechanisms involved in the pathogenesis and progression of osteosarcoma remain to be elucidated. Researchers have provided valuable insights into the tumorigenesis of Ribosomal protein S9 (RPS9) in some cancers. The purpose of this study was to elucidate the expression, functions, and mechanisms of RPS9 in human osteosarcoma. Methods: The expression of RPS9 in osteosarcoma tissues and cell lines was evaluated by qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Additionally, reduced expression of MLL3 is reported in breast tumors and gastric cancer [43, 44]. Ribosomal Protein S9 ( RPS9 ) is one of the first proteins that directly bind to the 18S rRNA and plays a crucial role in ribosome biogenesis [4547]. Inhibition of RPS9 activates p53 activity, it is suggested to be an efficient method to induce apoptosis in tumor cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, reduced expression of MLL3 is reported in breast tumors and gastric cancer [43, 44]. Ribosomal Protein S9 ( RPS9 ) is one of the first proteins that directly bind to the 18S rRNA and plays a crucial role in ribosome biogenesis [4547]. Inhibition of RPS9 activates p53 activity, it is suggested to be an efficient method to induce apoptosis in tumor cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway has also been demonstrated to have a key role in tumor cell survival and migration ( 34 ). Several drugs targeting the MAPK pathway have been reported to inhibit cell proliferation in osteosarcoma ( 35 ). The present study indicated that the Akt and MAPK pathways were activated in the drug-resistant cell line, and their activation was significantly inhibited following knockdown of TGM2.…”
Section: Discussionmentioning
confidence: 99%
“…Micrometer‐thick Ag‐PVA, Au‐PVA, Pt‐PVA, Pd‐PVA and Ag−Au‐PVA films have shown optical limiting effects comparable to colloidal solutions with a path length of several millimeters ,,,,, Pattern formation: Electron beam lithography has been used to generate nanoscale patterns through the in situ generation of Ag nanoparticles in a PVA thin film; such composites are likely to be of interest in plasmonic devices. Random laser: In situ fabricated Ag‐PVA thin films containing rhodamine 6G has been shown to be a highly cost‐effective design of a random laser with coherent feedback; recently, a white random laser has also been demonstrated Microwave absorber: Ag‐PVA thin film with ∼10% Ag content exhibits appreciable microwave absorption in the 8–12 GHz range …”
Section: Polymer – Metal/bimetal/semiconductor Nanocomposite Thin Filmsmentioning
confidence: 99%
“…Random laser: In situ fabricated Ag‐PVA thin films containing rhodamine 6G has been shown to be a highly cost‐effective design of a random laser with coherent feedback; recently, a white random laser has also been demonstrated …”
Section: Polymer – Metal/bimetal/semiconductor Nanocomposite Thin Filmsmentioning
confidence: 99%